STRUKTUR GINJAL IKAN SELAIS (OmpokhypopthalmusBleeker, 1846) DI PERAIRAN SUNGAI SIAK KOTA PEKANBARU - Wagiman '; Yusfiati '; Roza Elvyra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This study aims to find out histological condition of kidney tissue of selais fish (Ompok hypophthalmus) from Siak river. Kidney samples of the fish were collected from two stations, namely Siak I Bridge in Okura Village, District Rumbai Pesisir and Siak II Bridge Tampan Village, District Payung Sekaki. Histological slides with 6 μm thickness of the kidney samples of selais fish were made using paraffin method and stained with Hematoxylin-Eosin (HE). The kidney tissue of selais fish showed damages such as swelling of the glomerulus (12%), swelling of proximalis tubules cells (9.6%), swelling of loop of henle cells (6.5%), swelling of distal tubules cells (10.7%), swelling of macula densa cells (15.8%), a fatty of proximalis tubules cells (9.7%), a fatty of loop of henle cells (3.5%), a fatty of distal tubules cells (11.6%), congestion (6.15%) and necrosis (2.7%). Kidney tissue damages of selais fish occurred were allegedly affected by the heavy metal presence in the water of the Siak river.